Sistem Monitoring Level Air Galon Berbasis IoT Menggunakan Sensor Berat (Load Cell) - Alina Rusmiza; Sujono Sujono (Computer Journal, 2026)
This study develops an Internet of Things (IoT)-based monitoring system to measure water levels in gallon containers using a load cell as the primary weight sensor. The system enables users to monitor remaining water in real time and prevent unexpected shortages during daily activities. The method involves assembling hardware consisting of a load cell and an ESP32 microcontroller, followed by a calibration process to ensure accurate weight measurements. Programmed through the Arduino IDE, the ESP32 wirelessly transmits processed sensor data to a cloud platform such as Google Sheets or a hosting service for storage and management. Water levels are visualized through a web-based dashboard that presents data in a clear and accessible format. A notification feature alerts users when the gallon reaches a predefined minimum threshold. Experimental results show that the sensor consistently detects weight changes with stable performance throughout the monitoring process. The dashboard successfully displays real-time data reflecting the actual gallon condition. Overall, the system offers an effective and practical solution for automated water-level monitoring in households, offices, and small businesses.